+0  
 
0
119
1
avatar

Calculuate x from Log (x + 4) + log (3x + 2) = log 100 - 2log 2

 Jul 13, 2020
 #1
avatar+21957 
0

log(x + 4) + log(3x + 2)  =  log( (x + 4)(3x + 2) )  =  log( 3x2 + 14x + 8 )

 

log(100) - 2log(2)  =  log(100) - log(22)  =  log(100) - log(4)  =  log(100/4)  =  log(25)

 

Combining:  log( 3x2 + 14x + 8 )  =  log( 25 )

--->                        3x2 + 14x + 8  =  25

--->                        3x2 + 14x -17  =  0

--->                      (3x + 17)(x - 1)  =  0

 

--->     either  3x + 17  =  0            or     x - 1  =  0

                                x  =  -17/3     or           x  =  1

 

The answer  -17/3  doesn't check; the answer  1  does.

 Jul 13, 2020

18 Online Users

avatar